2018
DOI: 10.1590/1807-3107bor-2018.vol32.0054
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of oral and salivary parameters in patients with and without loss of bone mass

Abstract: Osteoporosis is an insidious and increasingly prevalent disease that can cause fractures and affect patients' quality of life. The current study comparatively evaluates patients with and without loss of bone mass in terms of salivary calcium, viscosity, and pH. A controlled cross-sectional study was conducted in two groups of 32 postmenopausal women subjected to a bone densitometry scan and later referred for dental management at the Federal University of Minas Gerais, Brazil. The patients were assigned to two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…So far, numerous papers have been published describing the levels of biomarkers associated with bone resorption and formation in various bodily fluids of patients with bone mineral changes [34][35][36][37][38][39][40]. In saliva, the following were the most frequently tested: N-telopeptide of type I collagen (NTX), C-telopeptide of type I collagen (CTX), salivary calcium, bone-specific alkaline phosphatase, and osteocalcin [37][38][39][40]. Some adverse effects of AR therapy on oral health have been highlighted recently; however, little is known about its potential side effects on the physicochemical properties of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…So far, numerous papers have been published describing the levels of biomarkers associated with bone resorption and formation in various bodily fluids of patients with bone mineral changes [34][35][36][37][38][39][40]. In saliva, the following were the most frequently tested: N-telopeptide of type I collagen (NTX), C-telopeptide of type I collagen (CTX), salivary calcium, bone-specific alkaline phosphatase, and osteocalcin [37][38][39][40]. Some adverse effects of AR therapy on oral health have been highlighted recently; however, little is known about its potential side effects on the physicochemical properties of saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 1373 full-text reports were not accessible among the 25 full-text articles we assessed for eligibility, 18 studies were subsequently excluded. 3 , 6 , 8 , 10 , 12 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Finally, 7 studies were included in a systematic review. 2 , 11 , 15 , 16 , 17 , 18 , 19 An overview of the search results and the screening process is summarized in the study flow chart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that post-menopausal women with a lower BMD had higher salivary calcium than post-menopausal women without bone mineral changes [88] or pre-menopausal or pregnant women [45]. Long-term supplementation of vitamin D combined with calcium, did not significantly affect salivary calcium in osteoporotic women [40].…”
Section: Calciummentioning
confidence: 98%
“…Limited, but promising, evidence was reported for salivary calcium and BMD in post-menopausal women, as those with lower a BMD had higher unstimulated calcium levels compared to premenopausal or pregnant women [45] or post-menopausal women without bone mineral changes [88]. This suggests that salivary calcium may be a useful screening tool for bone mineral changes and has the potential for early diagnoses of osteoporosis [88]. Unfortunately, as the included studies did not assess serum calcium levels, the relationship between salivary and serum calcium is currently unclear.…”
Section: Salivary Biomarkers and Nutritional Statusmentioning
confidence: 99%